Use of Moringa oleifera as a natural coagulant for turbidity removal in surface waters in the last 10 years: a review of the scientific literature (LACCEI, 2024)
Synthetic coagulants can generate harmful effects on the health of the population, in addition to presenting high costs and producing a large amount of sludge. Therefore, the present systematic review aims to determine the percentage of turbidity elimination in surface waters of Moringa oleifera as a coagulant, according to research journals published in scientific databases, in the last ten years. For this, several databases were consulted, which were Alicia, Dialnet, Google Scholar, ProQuest, Readlyn, Renati, ResearchGate, ScienceDirect and Scielo. Where, 50 scientific investigations were selected, which were filtered by inclusion criteria until finally obtaining 22 investigations between articles and theses, from which the pertinent information to the study was extracted. It was achieved as a result, that the coagulant obtained from the seed of Moringa oleifera presents a high percentage ranging between 70% and 99% of turbidity elimination in surface waters. Despite the difficulty that arose when translating foreign articles, it was concluded that Moringa oleifera as a natural coagulant has high levels of turbidity elimination percentages in surface waters, especially if the seeds are adequately prepared to obtain the coagulant.